Analysis of Determinants of Puskesmas Drug Availability in South Sorong District Year 2024 - Tonglo, Ruhama Utami; Uly, Nilawati; Iskandar, Ishaq; Zamli, Zamli (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Drug availability at Puskesmas (Community Health Centers) is essential for delivering quality public health services. Multiple factors such as the roles of doctors, pharmaceutical personnel, patients, and drug distributors are thought to influence this availability. Objectives: This study aimed to analyze the determinants affecting drug availability at Puskesmas in South Sorong Regency in 2024. Methods: A quantitative approach was used, with data analyzed through statistical tests including the T-test, F-test, and coefficient of determination to assess both partial and simultaneous effects of the independent variables. Results: The analysis revealed that there were no significant partial or simultaneous effects of the roles of doctors, pharmaceutical personnel, patients, and drug distributors on drug availability (p > 0.05). The coefficient of determination (R²) was 0.153, indicating that only 15.3% of the variation in drug availability could be explained by these factors. Conclusions: The study concludes that the roles of doctors, pharmaceutical personnel, patients, and drug distributors have no significant influence on drug availability at Puskesmas in South Sorong Regency. The low coefficient of determination suggests that other unexamined factors may play a more dominant role in determining drug availability in these health facilities.